Effect of coadministered fat on the tolerability, safety and pharmacokinetic properties of dihydroartemisinin-piperaquine in Papua New Guinean children with uncomplicated malaria - Moore, Brioni; Benjamin, J.; Salman, S.; Griffin, S.; Ginny, E.; Page-Sharp, Madhu; Robinson, L.; Siba, P.; Batty, Kevin; Mueller, I.; Davis, T. (American Society for Microbiology, 2014)
Coadministration of dihydroartemisinin-piperaquine (DHA-PQ) with fat may improve bioavailability and antimalarial efficacy, but it might also increase toxicity. There have been no studies of these potential effects in the pediatric age group. The tolerability, safety, efficacy, and pharmacokinetics of DHA-PQ administered with or without 8.5 g fat were investigated in 30 Papua New Guinean children aged 5 to 10 years diagnosed with uncomplicated falciparum malaria. Three daily 2.5:11.5-mg-base/kg doses were given with water (n = 14, group A) or milk (n = 16, group B), with regular clinical/laboratory assessment and blood sampling over 42 days. Plasma PQ was assayed by high-performance liquid chromatography with UV detection, and DHA was assayed using liquid chromatography-mass spectrometry. Compartmental pharmacokinetic models for PQ and DHA were developed using a population-based approach. DHA-PQ was generally well tolerated, and initial fever and parasite clearance were prompt. There were no differences in the areas under the concentration-time curve (AUC0–∞) for PQ (median, 41,906 versus 36,752 μg • h/liter in groups A and B, respectively; P = 0.24) or DHA (4,047 versus 4,190 μg • h/liter; P = 0.67). There were also no significant between-group differences in prolongation of the corrected electrocardiographic QT interval (QTc) initially during follow-up, but the QTc tended to be higher in group B children at 24 h (mean ± standard deviation [SD], 15 ± 10 versus 6 ± 15 ms0.5 in group A, P = 0.067) and 168 h (10 ± 18 versus 1 ± 23 ms0.5, P = 0.24) when plasma PQ concentrations were relatively low. A small amount of fat does not change the bioavailability of DHA-PQ in children, but a delayed persistent effect on ventricular repolarization cannot be excluded.